Students’ Perceptions on Teachers’ Teaching Strategy and Their Effects towards Students’ Achievement - M Zaim; Refnaldi Refnaldi; Ria Rahmiyanti (International Journal of Research in Counseling and Education, 2020)
Teaching strategy is necessary for the teaching and learning process. It is used as a way to present learning content in a way that engages the learners. It is assumed that applying appropriate teaching strategies has a positive impact on students' achievement. This study aimed to analyze students' perceptions of teacher's teaching strategy and its effect on students' achievement in learning English. This study was an Ex-post Facto study. The population of this study was the students who had studied English as a general subject at Universitas Negeri Padang in the academic year of January-June 2019. Cluster random sampling was used with 150 students as the sample of this study. Then, for collecting the data, two questionnaires and documents of students’ final scores were used as the instruments. The data was analyzed by using a Likert-type scale and regression linear statistical analysis through IBM SPSS Statistics 22 Software. The results showed that generally, students' perception of the teacher's teaching strategy was High. Then, based on the statistical analysis, it was found that thevalue of F-count was lower than F-table. It meant that the null hypothesis (H0) was accepted, and the alternative hypothesis (Ha) was rejected. Thus, there was no significant effect of student's perception of teaching strategy towards students' achievement in learning English as a general subject.